2000
DOI: 10.1002/1521-396x(200005)179:1<159::aid-pssa159>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Study of Bandgap Energy Levels in CdTe Films Electrodeposited from Chlorine-Containing Solutions

Abstract: Thin films of CdTe are electrodeposited at different temperatures and potentials on stainless steel foil substrates from a 1M CdSO 4 solution containing chlorine (0.03 to 0.06 M). Current±voltage, conductivity±temperature and photoinduced current transient spectroscopy measurements have been performed on devices formed by evaporation of semitransparent Au electrodes on CdTe. The bandgap energy levels in these films have a distinctly different spectrum compared to films deposited from Cl-free solutions. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 21 publications
2
7
0
Order By: Relevance
“…CdTe solar cells with Cu-evaporated back contacts demonstrated the capacitance peaks at a frequency of 100 kHz indicating the trap charge builds up due to deep levels. After incorporating the temperature dependence of cross-section in a) Email: prk6@njit.edu 0021-8979/2013/113(14)/144504/6/$30.00 V C 2013 AIP Publishing LLC 113, 144504-1 the activation energy, the observed deep levels were attributed to doubly ionized cadmium vacancies and Cu-related sites identical to reported experimental results 9,12,15,[20][21][22][23][24][25][26][27] obtained for deep defects. It is demonstrated that TDCS offers a rapid and convenient means of detecting and characterizing the properties of the deep centers.…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…CdTe solar cells with Cu-evaporated back contacts demonstrated the capacitance peaks at a frequency of 100 kHz indicating the trap charge builds up due to deep levels. After incorporating the temperature dependence of cross-section in a) Email: prk6@njit.edu 0021-8979/2013/113(14)/144504/6/$30.00 V C 2013 AIP Publishing LLC 113, 144504-1 the activation energy, the observed deep levels were attributed to doubly ionized cadmium vacancies and Cu-related sites identical to reported experimental results 9,12,15,[20][21][22][23][24][25][26][27] obtained for deep defects. It is demonstrated that TDCS offers a rapid and convenient means of detecting and characterizing the properties of the deep centers.…”
Section: Introductionsupporting
confidence: 73%
“…Since the deep level associated with doubly charged cadmium vacancy was observed, it may be postulated that vacancy formation was suppressed, and the creation of interstitial favored in our devices. Rakhshani and Makdisi 25 have investigated the trap level with activation energy (0.88 eV) and r t $ 1.1 Â 10 À11 cm 2 in CdTe thin-film solar cells. In an earlier work, 9 we also observed this trap level.…”
Section: Resultsmentioning
confidence: 99%
“…5͑a͒ and 5͑b͔͒ work together; at the end, only the left-hand side process acts. An acceptor level at 0.090 eV above the valence band, owing to the Ag-V Cd 2Ϫ /Cl Te ϩ complex has been recently reported, 19 which supports the model proposed in Fig. 5.…”
Section: Discussionsupporting
confidence: 84%
“…Cadmium vacancies (V cd ) tend to form A -center with Cl donor leaving concentration of isolated V cd are low. In addition, this shallow trap levels seems to be associated with a hole trap as the activation energy of this defect was also observed by Photo induced current transient spectroscopic (PICTS) [15,16].…”
Section: Current Transientsmentioning
confidence: 99%
“…This further confirms the presence of this shallow trap level. In addition, it is clearly associated with hole trap, observed earlier by Photo induced current transient spectroscopic (PICTS) method [16,17].…”
Section: Capacitance Transientsmentioning
confidence: 99%